Photo-induced ultrafast active ion transport through graphene oxide membranes - Jinlei Yang (Nature Portfolio, 2019)
Ionic transport through subnanometer-sized channels in 2D material-based membranes can be exploited for energy and separation applications. Here the authors demonstrate the visible light activation of an ultrafast ionic flux against a concentration gradient in graphene oxide membranes.